Adventure-Based Leadership Training Development Model for Management Trainee Employees at FASEL.Inc - Dian Wibowo Utomo; Serafin Wisni Septiarti (Educenter : Jurnal Ilmiah Pendidikan, 2026)
Leadership development programs increasingly require experiential approaches that foster not only cognitive understanding but also behavioral transformation. Conventional classroom-based leadership training often lacks contextual and emotional engagement, particularly for management trainee programs. This study aims to describe and analyze an adventure-based leadership training model and to formulate the APPEEM model (Assess, Plan, Prepare, Event, Evaluation, and Monitoring) implemented by FASEL.Inc for management trainee leadership development. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, participant observation, and document analysis involving trainers, facilitators, and management trainees. Data analysis was conducted using the Miles and Huberman interactive model, while data credibility was ensured through triangulation of sources, techniques, and time. The findings indicate that the APPEEM model provides a structured and systematic framework for implementing adventure-based leadership training grounded in experiential learning principles. The model facilitates leadership skill development through progressive stages, reflective learning, and continuous monitoring. This study contributes a practical and conceptual model that can be adopted and adapted by organizations seeking alternative leadership training approaches beyond conventional methods.